Complexity in cognitive assessment of elderly British minority ethnic groups: Cultural perspective. (July 2014) - Khan, Farooq; Tadros, George
Aim: To study the influence of cultural believes on the acceptance and accessibility of dementia services by patients from British Minority Ethnic (BME) groups. Results: It is noted that non-White ethnic populations rely more on cultural and religious concepts as coping mechanisms to overcome carer stress. In British Punjabi families, ageing was seen as an accepted reason for withdrawal and isolation, and cognitive impairment was rarely identified. Illiteracy added another complexity, only 35% of older Asians in a UK city could speak English, 21% could read and write English, while 73% could read and write in their first language. False positive results using Mini Mental State Examination was found to be 6% of non-impaired white people and 42% of non-impaired black people. Cognitive assessment tests under-estimate the abilities in BME groups. Wide range of variations among white and non-White population were found, contributors are education, language, literacy and culture-specific references.